JOB CONDITIONS AND PERFORMANCE OF HEALTH CENTRE IV WORKERS IN SELECTED DISTRICTS OF SOUTH WESTERN UGANDA: A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Atwiine, Johnson; Atukunda, Gershom; Mwesigye, Jimmy; Asiimire, Donath (Student's Journal of Health Research Africa, 2024)
Background Many nations have reduced the precarious number of doctors, nurses, and midwives to 2.3 per 1,000 people. Care must be taken to ensure that essential health services are handled satisfactorily (Jimba et al., 2010; Karwowski & Marras, 1998; WHO, 2016). The purpose of this study is to investigate the connection between Health Center IV employees' performance and their working circumstances in a few Southwestern Ugandan districts. Methods This study adopted a descriptive cross-sectional study with both quantitative and qualitative approaches to data collection and analysis. A sample size of 215 respondents consisting of health workers, political leaders, end-users, and supervisors participated in this study. The data was collected using the questionnaire survey and interview method. It was also analyzed using both SPSS v.25 and Nvivo statistical packages respectively. Results The results revealed a positive and significant association between job conditions and performance. In regards to the elements of job conditions, working conditions, and job security were established to be significant predictors of health center IV worker’s performance, while training and autonomy were not. Conclusion The findings disclosed that both job security and work environment are significant and positive predictors of health center IV workers’ performance. This means that any positive changes in job security and work environment are associated with positive changes in workers' performance. Nonetheless, job security matters most. This means that the work environment such as working conditions, office layout, and design, workload, health materials/kits, and equipment once provided to different health centers enhance performance in terms of reliability of health workers and improvement on their productivity. Recommendation Therefore, the study recommends that health management officers should develop good health policies, working terms, and strategies for the entire health workers at all levels for better health service delivery for all citizens in Uganda.